IMPLEMENTASI PEMBERIAN BANTUAN HUKUM BAGI MASYARAKAT TIDAK MAMPU OLEH POSBAKUM AISYIYAH JAKARTA - Setya Mawarni, Heni; Jamaludin, Ujang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to find out the implementation of providing legal aid for the poor by Posbakum Aisyiyah Jakarta, identify obstacles or obstacles faced in its implementation, and analyze the community's response to the existence of these services. The research method used is a qualitative method with data collection techniques through observation, interviews, and documentation. With resource persons consisting of paralegals, advocates and the community. The results showed that the implementation of legal aid provision in Posbakum Aisyiyah Jakarta consists of litigation and non-litigation, where the provision of litigation legal aid starts from the registration mechanism, verification of recipient criteria, and trial assistance by advocates free of charge. As well as non-litigation in the form of consultation, counseling and legal education. The main obstacles faced include limited human resources and limited operational funding. However, the response of the justice-seeking community to Aisyiyah Jakarta's Posbakum service has been very positive, as this service helps improve access to justice for the poor. This research is expected to serve as a reference in efforts to develop more effective and sustainable legal aid services.